Evaluation of a newly developed flipped-classroom course on interprofessional practice in health care for medical students - Anita V. Thomae; Lotte Verweij; Claudia M. Witt; David Blum; Emanuel Feusi; André Fringer; Marion Huber; Melanie Roos; Jasmin Anita Lal; Rahel Naef (Medical Education Online, 2023)
ABSTRACTInterprofessional education is expected to promote collaborative practice and should therefore be included in health professionals’ curricula. Reports on interprofessional curricular development and its evaluation are rare. We therefore undertook a comprehensive quantitative and qualitative evaluation of a new, mandatory course on interprofessional collaboration for medical students during their third year of the Bachelor of Medicine study programme. The newly developed and implemented course spans over six weeks and was designed in a hybrid, flipped-classroom format. It incorporates experience- and case-based learning as well as interactions with other health professionals. Each student completes an eLearning and a clinical workshadowing individually before attending the – due to the pandemic – virtual live lectures. To assess quality and usefulness of teaching-learning formats and course structure to learn about interprofessional collaboration and to develop interprofessional competencies and identity, a quantitative and qualitative evaluation was performed with more than 280 medical students and 26 nurse educators from teaching hospitals using online surveys (open & closed-ended format). Data were analyzed descriptively and using content analysis processes. Students appreciated the flipped-classroom concept, the real-world case-based learning scenarios with interprofessional lecturer teams, and the possibility of an experience-based learning opportunity in the clinical setting including interaction with students and professionals from other health professions. Interprofessional identity did not change during the course. Evaluation data showed that the course is a promising approach for teaching-learning interprofessional competencies to medical students. The evaluation revealed three factors that determined the success of this course, namely, a flipped-classroom concept, the individual workshadowing of medical students with another health professional, mainly nurses, and live sessions with interprofessional teaching-learning teams. The course structure and teaching-learning methods showed potential and could serve as a template for interprofessional course development in other institutions and on other course topics.